Bilirubin injury to neurons: contribution of oxidative stress and rescue by glycoursodeoxycholic acid - Brito, Maria A. (2015)
It is well established that high levels of unconjugated bilirubin (UCB) can be toxic to the central nervous system, and oxidative stress is emerging as a relevant event in the mechanisms of UCB encephalopathy. In contrast, the hydrophilic bile acid, ursod